Kontrol diri pada siswa SMK Wringinjajar - Safitri, Dewi (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2023)
Self-control possessed by adolescents will be influenced by many factors both internally and externally. The purpose of this study was to analyze the relationship between the intensity of playing online games with students' self-control. This research method uses a type of cross sectional research with quantitative research. The population in this study is students of SMK Ki Ageng Wringinjajar, Demak Regency in 2023. Data collection techniques in this study used questionnaires. The data analysis technique in this study used pearson correlation. The results showed that the intensity of playing online games has a significant relationship with self-control in students of SMK Ki Ageng Wringinjajar, Demak Regency in 2023. The test results found that the intensity of playing online games had a very high relationship with the level of self-control of students. The direction of the relationship between the two variables is in the opposite direction or not in the same direction. The conclusion in this study is that students' self-control can be explained through the level of intensity of playing online games in students of SMK Ki Ageng Wringinjajar, Demak Regency in 2023.